Spin-based magnetic random-access memory for high-performance computing - Cai, Kaiming (2024)
Memory serves as a critical component in today’s electronic systems for data storage and processing. In traditional computer architectures, the logic and memory units are physically separated, due to the performance gap in operational speed and capacity among memories, resulting in the fundamental limitation of the von Neumann computers. Moreover, with the evolution of CMOS technology nodes, transistors become smaller and smaller, to improve the operational speed, area density and energy efficiency, while supplying lower driver currents. However, the mainstream technologies, such as embedded-Flash and SRAM, are facing significant scaling and power consumption issues. A denser and more energy efficient embedded memory would be highly desirable, specifically for advanced technology nodes of 14 nm or beyond. In contrast to conventional electronic devices, manipulating electric charges in non-magnetic semiconductors to process information, spintronic devices are based on the spin of electrons, offering innovative computing solutions. To incorporate spintronics into the existing mature semiconductor technology, the spin-based devices are generally designed with a core structure of a magnetic tunnel junction, which functions as magnetic random access memory (MRAM).